Extração de antioxidantes do café verde (Coffea canephora) e aplicação em produtos cárneos cozidos - Moura, Sthefanie Oliveira de (2023)
Sausages have a composition rich in proteins, lipids and iron that make them susceptible to oxidation, causing negative sensory changes. In this way, additives have become allies of processed products. However, today there is a worldwide concern with food choices considered healthy, safe and natural. In addition, the use of synthetic preservatives, such as antioxidants, has been questioned, due to studies that indicate an association with the development of diseases. This led to the search for the use of natural additives. In this work, the association of different solvents with the US and shaker techniques was investigated in order to achieve an extract of Coffea canephora rich in antioxidants. Ten solvents were tested (water, ethanolic solution 34.2% (ET 34.2%), and 8 natural eutectic solvents synthesized with different combinations of choline chloride, acetic acid, citric acid, lactic acid and glucose), generating 20 treatments. Of the 20 extracts, ethanol (ET) 34.2% and water under agitation provided the extracts with the highest total phenolic content using the Folin Ciocalteau method and antioxidant potential by the DPPH, ABTS and FRAP methods, with extracts with stable antioxidant activity being observed even extracted from green coffee beans stored under freezing for a period of one year. The selected extracts were applied to the cooked sausage meat product. The formulations were given through the application of spray-dried aqueous and ethanolic extracts in proportions of 0.3% and 0.8% (EA 0.3%, EA 0.8% and EE 0.3% and EE 0. 8%, respectively) and a standard formulation (P) (0.1% sodium erythorbate) for control. The samples were analyzed for chemical composition and sensory acceptance by the hedonic scale test and purchase intention, color, pH, water activity (Aw) and oxidative stability by the TBARS method (substances reactive to acid. 2-thiobarbituric acid) for 60 days (with an interval of 15 days) of storage at 21 ºC ± 1. There was no significant difference (p ≤ 0.05) in the centesimal composition of the samples, all of which were in accordance with current legislation. During storage, the samples differed significantly (p ≤ 0.05) for color, with higher values of L*, a* and b* for the P sample. After 60 days, the formulations had a pH between 6.01 and 6.15, with exception of EE 0.8%, which presented pH 5.58 (p ≤ 0.05). All samples showed a reduction in Aw and a significant difference (p ≤ 0.05) in TBARS values, with EE 0.8% (0.09 mg/Kg) and EE 0.3% (0.12 mg / Kg) with lower lipid oxidation, followed by samples EA 0.3% (0.21 mg/Kg), EA 0.8% (0.26 mg/Kg) and P (0.45 mg/Kg), but all within the recommended parameters for the product. The average acceptance in the sensory analysis on a 9-point scale was above 7 for all samples (p ≤ 0.05). Therefore, the application of aqueous or ethanolic extract of green canephora coffee obtained from extraction in shaker, dried by spraying, in proportions of 0.3 to 0.8% are a viable alternative for the replacement of synthetic antioxidants in meat product pepperoni type sausage, the use of which may be extended to other cooked meat products of similar composition. The use of deep eutectic solvents showed promise; however, they can be explored in other compositions and extraction conditions in order to obtain better results.